Tinjauan Fiqh Muamalah terhadap Hutang (Qardh) Bersyarat dalam Jual Beli Gambir (Studi Kasus di Nagari Sialang Kecamatan Kapur IX, Kabupaten Lima Puluh Kota) - Aliya Lola Efika; Sofia Ridha (AHKAM, 2026)
The practice of conditional debt (qardh) in the sale of gambir is a common phenomenon among gambir farmers and collectors in Nagari Sialang, Kapur IX Subdistrict, Lima Puluh Kota Regency, arising from farmers’ limited capital to meet production costs and living needs during the harvest period. In this practice, the debt is accompanied by a condition requiring farmers to sell their gambir harvest to the lending collector at a unilaterally determined price below the market rate, thereby creating potential transactional injustice. This study aimed to analyze the practice of conditional debt in gambir trading and to examine it from the perspective of fiqh muamalah. The research employed field research with a descriptive qualitative approach. Data were obtained through in-depth interviews and direct observations of gambir farmers and collectors, then analyzed through the stages of data reduction, data display, and conclusion drawing. The findings show that this conditional debt practice leads to farmers’ economic dependence on collectors, the loss of farmers’ freedom in choosing buyers, and price injustice. From the perspective of fiqh muamalah, although the debt contract (akad qardh) formally fulfills the pillars and conditions, the stipulation that yields economic benefit for the lender renders the practice impermissible because it contains elements of riba and contradicts the principles of tabarru’ and justice in Islam. The implications of this study underscore the need for education on muamalah according to Islamic law and the development of fairer and more sustainable transactional models for gambir farmers.